PEMANFAATAN GAMIFIKASI DALAM PEMBELAJARAN PENDIDIKAN ISLAM: MEMBANGUN MOTIVASI SISWA DALAM MENGHAFAL AL-QUR'AN - I.M. Fatimah Zahro (Kopertais Wilayah VII Palembang, 2024)
This paper explores the use of gamification in Islamic education, particularly in motivating students to memorize the Qur'an. Memorizing the Qur'an is a central element in Islamic education, but students often face challenges due to monotonous learning methods. Gamification, the integration of game elements such as points, rewards, and challenges into non-game contexts, has been identified as a potential tool to increase motivation and engagement in the learning process. This study employs a systematic literature review (SLR) approach to evaluate existing research on gamification's application in Islamic education. The findings show that gamification significantly enhances students' intrinsic motivation and engagement, creating a more interactive and enjoyable learning environment. Several educational applications, such as